MICROFINANCE AND FINANCING OF MICRO-ENTREPRENEURSHIP IN BURUNDI - Théogène Nsengiyumva (Journal of Management Small and Medium Enterprises (SMEs), 2023)
This article aims to identify the determinants of financing microenterprises in Burundi by microfinance institutions. Using the logit model and exploiting data from the loan portfolios of Burundian microfinance institutions, the econometric analysis reveals that the financing of microenterprises in Burundi is strongly correlated with characteristics of these and/or those of their micro-entrepreneurs on one hand, and to the nature of the guarantee presented when applying for credit on the other hand. We conclude by saying that the consolidation of public financial support, the establishment of monitoring policies for these guarantee funds, and the involvement of all stakeholders could substantially improve the financing of microenterprises in Burundi. Keywords: Microfinance; Credit; Micro-entrepreneurs; Microbusiness; Burundi